Mengenal Investasi: Edukasi Masyarakat untuk Menghindari Investasi “Bodong” di Kecamatan Boliyohuto, Kab. Gorontalo - Nurul Fadhilah; Bela Mamonto; Mustaqim Idrus; Yulfika Daud; Rayyan Mamonto; Tian Lahay; Ranti Amsati; Wahyu Palowa; Rifadli D. Kadir; Iskandar Abbas (Komunal Jurnal Pengabdian Masyarakat, 2023)
Investment aimed to manage assets and increase people's income from the profit earned. The expected return depends on the investment instrument and the level of risk. The higher the risk, the higher the rate of return. On the contrary, the lower the risk, the lower the return on investment. This principle should be well-introduced to the public in order to avoid "fraud" investments. Cases of fraud of investment that went viral in the society are the portrait of the level of understanding of the society about investment and its risks. This study was conducted from the act of community service activities in Boliyohuto District, Region of Gorontalo.